2016
DOI: 10.1007/s12665-016-5453-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons in surface sediments of harbor areas in a tropical region (Ceará state, northeast Brazil)

Abstract: Sediment samples collected in two harbors of a tropical region of Brazil were investigated for the distribution of linear alkylbenzenes (LABs), aliphatic (AHs) and polycyclic aromatic hydrocarbons (PAHs). The levels of hydrocarbons in sediments from Mucuripe and Pecém harbors were lower than those reported in industrialized sites and threshold levels of sediment quality guidelines. Analysis of AHs revealed an input of biogenic compounds and, according to diagnostic ratios, PAHs in both harbors originated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
6
1
Order By: Relevance
“…Prior to dredging activities, higher concentrations of Hg, Cd, Cu, Ni, Zn, and PAHs were observed in sediments of Mucuripe Bay (Buruaem et al, 2012(Buruaem et al, , 2016. Contamination levels were higher compared to those found in this study and they were also associated with acute toxic effects on T. viscana, and with chronic effects of liquid phases observed on the larval development of L. variegatus (Moreira et al, 2017).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Prior to dredging activities, higher concentrations of Hg, Cd, Cu, Ni, Zn, and PAHs were observed in sediments of Mucuripe Bay (Buruaem et al, 2012(Buruaem et al, , 2016. Contamination levels were higher compared to those found in this study and they were also associated with acute toxic effects on T. viscana, and with chronic effects of liquid phases observed on the larval development of L. variegatus (Moreira et al, 2017).…”
Section: Resultscontrasting
confidence: 57%
“…Most of treatments exhibited monotonic responses, especially for the hydrocarbons in MD1 (surveys 1 and 2) and MD3 (survey 2). Relevant sources of hydrocarbons including volatile compounds were related to harbors activities, effluent from an oil refinery and the inputs from the drainage system of urban runoff (Cavalcante et al, 2010;Buruaem et al, 2016). Levels of inorganic chemicals found in this study were like those found in A. flexusoa sampled in the estuaries of Potengi and Curimataú rivers, both located in Rio Grande do Norte state (NE Brazil) and affected by urban activities (Silva et al, 2006).…”
Section: Resultssupporting
confidence: 53%
“…The compounds were quantitatively analyzed using an Agilent 6890 gas chromatograph coupled to a 5973N mass spectrometer (GC/MS). More details of sediment analysis are described in previous studies (Buruaem et al, 2016;Saes et al, 2019). The validation of analytical methods was assured by the analysis of surrogates, blank samples, and the reference materials of the National Institute of Standards and Technology for metals (NIST SRM 1646a), and hydrocarbons (NIST SRM 1944).…”
Section: Sediment Analysismentioning
confidence: 99%
“…The main harbor of the state is situated within the bay and its waters receive substances from urban and industrial activities (e.g. an oil refinery) (Buruaem et al, 2012(Buruaem et al, , 2016. Sediments of MB are mainly sandy but the presence of jetties close to the harbor have caused an increased deposition of fine particles and other materials, including contaminants (Maia et al, 1998;Moreira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sediments from the stations situated in the shade portion of the Mucuripe Harbor of the port (MD1, MD1', MD2 and MD2') were more muddy, organically enriched and contaminated by metals and hydrocarbons (Buruaem et al, 2016) (Figure 2; Table 1). The sediment from MD1 exhibited the highest concentration of Hg, Pb, Cr, Cu, Ni and Zn (Buruaem et al, 2017), whereas MD2 presented intermediary levels, with lower concentrations in MD3 (Buruaem et al, 2012).…”
Section: Discussionmentioning
confidence: 99%